1997
DOI: 10.1007/bf00941814
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic perforation of the gallbladder: Report of a case and a review of the Japanese literature

Abstract: A 79-year-old man was admitted to our hospital because of severe epigastric pain. Ultrasonography and computed tomography revealed a slightly distended gallbladder with a small amount of free intraabdominal fluid. At emergency laparotomy, perforation of the gallbladder was recognized and thus a cholecystectomy was performed. Histopathologically, localized necrosis was seen at the site of perforation: however, the inflammation of the surrounding tissue was mild and no thrombus was detected within the intramural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 3 publications
0
21
1
Order By: Relevance
“…1,2 It is not possible to predict reliably in which patients this complication will develop. 8 Acute uncomplicated cholecystitis is more common among females, with a female to male ratio of two to one: However, GBP is more frequent in the male gender. 1,9,10 Study reported that there were a greater number of men than women with type I and type II perforations, as compared to those with type III perforations.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is not possible to predict reliably in which patients this complication will develop. 8 Acute uncomplicated cholecystitis is more common among females, with a female to male ratio of two to one: However, GBP is more frequent in the male gender. 1,9,10 Study reported that there were a greater number of men than women with type I and type II perforations, as compared to those with type III perforations.…”
Section: Discussionmentioning
confidence: 99%
“…In one review, a correct diagnosis was established preoperatively in only one of the nine (11.1%) patients. 7 The fundus is the most common site of perforation, probably because it is the most distal part with regards to blood supply. Furthermore, some systemic diseases, such as atherosclerotic heart disease, may induce ischemia of the gallbladder wall, leading to necrosis and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic and spontaneous perforation of acalculous gallbladder is very rare [1,2]. Mostly, gallbladder perforation is due to inflammation, trauma, or obstruction [3].…”
mentioning
confidence: 99%
“…Mostly, gallbladder perforation is due to inflammation, trauma, or obstruction [3]. Perforation of gallbladder can be classified into three groups: [1] Spontaneous, [2] Traumatic, and [3] iatrogenic. The spontaneous group is further sub-divided into an idiopathic group and a secondary group, which includes acute inflammation, infection, lithiasis, congenital obstruction, and anticoagulant therapy, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation